Uji Efektivitas Ekstrak Daun Tapak Dara Terhadap Penyembuhan Luka Sayat Pada Kulit Punggung Kelinci - Samodra, Galih; Kaaffah , Silma (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Incision wounds are a form of damage to body tissues caused by sharp objects and can cause bleeding by involving the role of hemostasis so that inflammation occurs. One medicinal plant with potential as traditional medicine is the Catharanthus roseus leaf because it contains secondary metabolites such as alkaloids, flavonoids, saponins, and steroids. This study aims to determine the effect of Catharanthus roseus leaf extract on the healing of wounds on the skin of rabbit backs. Observations were made for 14 days on three rabbits whose backs were divided into six areas. In certain areas, it is wound along 2 cm with a depth of 0.1 cm to apply Catharanthus roseus leaf test ointment 2 times a day. Rabbits were tested with five treatment groups: extract concentration of 25%, 50%, and 75%, and positive control and negative control. The results showed that the wounds were positive by days 8 and 9, 75% concentration had closed, and all rabbits had no scabs. The results of statistical tests showed that blood tread leaf extract affected the parameter of wound length in rabbits, which was 0.000 (p˂0.05). It can be concluded that the preparation of Catharanthus roseus leaf extract with concentrations of 25%, 50%, and 75% provides the effectiveness of healing incision wounds in rabbits.